PENGOPTIMALAN PERANCANGAN PESAWAT UAV (QUADCOPTER) TERHADAP BERAT TOTAL YANG BERPENGARUH PADA ESTIMASI WAKTU TERBANG - Riza Arif Pratama Riza; Indra Permana; Muhammad Ikhsan; Sahid Bayu Setiajit (Sekolah Tinggi Teknologi Kedirgantaraan, 2023)
The design of a UAV (Quadcopter) aircraft must be carried out in a structured and systematic manner. Existing parameters must be estimated properly so that the design in the selection of UAV aircraft components can be optimized. Optimization in terms of system design is able to maximize the workability of components. The total weight of the UAV aircraft greatly affects the level of ability to estimate the time when flown. Battery consumption will be higher if the system capabilities are not balanced and the components require large power capacity to operate. Increasing the Estimated Flying Time (EWT) really needs to be done so that UAV aircraft are able to fly for a long time. Research that has been done by EWT averages under 15 minutes to air. UAV aircraft design simulation is used to calculate EWT. EWT calculations are carried out to find out which components can reduce their power consumption without reducing their maximum capacity. The design is simulated with specifications below the average of the related research. The results of the simulation of the UAV aircraft weighing 3 kg showed an increase in the estimate of 65% or 8 minutes longer than the related research. The specifications replaced are batteries and brushless motors.